1979
DOI: 10.1159/000232249
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of IgE Antibody Formation in the Rabbit by Adrenergic Antagonists

Abstract: The effects of adrenergic antagonists on the humoral immune response of rabbits to egg albumin was studied. Propranolol, a β-adrenergic antagonist, when administered at a dosage of 20 mg/kg of body weight, enhanced both passive hemagglutinating and IgE (passive cutaneous anaphylaxis) antibody formation. Phenoxybenzamine, an α-antagonist, at 0.4–40 mg/kg had a similar adjuvant effect. A marked delay in the immune response was noted with high dosages of phenoxybenzamine. Possible mechanisms of the adjuvant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Medication with the P-receptor blocking agent propranolol during the first trimester of pregnancy has been reported to be associated with an increased risk of allergy in the children (5). This observation is interesting because P-receptor blockade may enhance IgE antibody formation in animals (46,66).…”
Section: Pre-and Perinatal Risk Factorsmentioning
confidence: 99%
“…Medication with the P-receptor blocking agent propranolol during the first trimester of pregnancy has been reported to be associated with an increased risk of allergy in the children (5). This observation is interesting because P-receptor blockade may enhance IgE antibody formation in animals (46,66).…”
Section: Pre-and Perinatal Risk Factorsmentioning
confidence: 99%
“…Thus, it has been reported that administration of the p-adren ergic antagonists propranolol and phenoxybenzamine enhances IgE antibody formation in rabbits [10]. It has also been reported that addition of propranolol to human blood lymphocytes in vitro causes in creased IgE production [II], (I-Adrenergic receptor-blocking drug agents, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, IgE production can be enhanced by treatment with beta-receptor blockers (5,17) and a beta-receptor stimulating agent can decrease IgE production (17). The results of the present study indicate that, under certain conditions, the in vitro IgE synthesis of human lymphocytes increases when a beta-receptor inactivated calf serum.…”
mentioning
confidence: 54%